PENDAMPINGAN UMKM TERDAMPAK GEMPA CIANJUR 2022 DAN PEMANFAATAN APLIKASI DONASI DIGI-FASCH - Endah Lisarini; Hanisa Sismaya Lestari; Asep Saepul Alam; Rahmat Taufiq Dwi Jatmika; Rosda Malia (LPPM Universitas Bina Bangsa, 2023)
Not a few MSMEs in the Cugenang subdistrict, Cianjur regency stopped operating due to the 2022 Cianjur earthquake. By looking at their potential to revive, it is deemed necessary to provide assistance. Assistance was provided to 12 selected MSMEs, namely MSMEs that had never received assistance from any party but had great potential to be revived after the earthquake. Assistance includes business planning, business licensing, digital marketing including opening an online shop and preparing financial reports. Apart from the assistance provided by lecturers and students of the Faculty of Applied Science (FASTER) Suryakancana University (UNSUR), financial assistance was also provided to MSMEs collected from community donations through the Digi-Fasch donation application. The objectives of the assistance are: 1) Help 12 MSMEs affected by the Cianjur earthquake in Sarampad and Benjot villages, Cugenang sub-district through community donations collected from the Digi-fasch application; and 2) Increase insight into MSMEs regarding digital marketing and doing business (selling) through online media. Mentoring is carried out using lecture, discussion, tutorial, and demonstration methods equipped with mentoring modules including modules: on business planning in the form of goods, business planning in the form of services, determining a marketable business name, company business licensing (PT), business licensing in the form of CV, business licensing individual, logo design, packaging, labels, packaging, marketplace types, creating a shop account on Tiktok, creating promotional content on social media, digital marketing, preparing MSME financial reports, cash flow reports and profit loss reports. To determine the success of mentoring, 1) pre-test before mentoring and post-test afterward; 2) monitoring and evaluation. The results of the assistance show that 1) 12 MSMEs were helped in reactivating their businesses through assistance and donations; 2) There is an increase in skills and positive attitudes towards managing MSMEs digitally